2017
DOI: 10.1007/s00268-017-4190-5
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Leagues—A Novel Option to Attract Medical Students to a Surgical Career

Abstract: Participation in Trauma League has been an effective strategy to encourage medical students to choose a career in general surgery in Campinas, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
(59 reference statements)
0
8
0
1
Order By: Relevance
“…Previous studies assessing potential means of stimulating interest in orthopaedics and other surgical specialities among medical students have demonstrated that practical and interactive experiences during medical school effectively stimulate interest in pursuing a future surgical career. 2 , 9 , 15 These studies have highlighted the importance of positive interaction with surgical professionals: this can be teaching-based aimed at increasing clinical or career-based knowledge, take the form of interactive practical skills sessions, or via mentorship relationships between surgeons and students. A recent study in Brazil demonstrated the beneficial impact of societies tasked with increasing knowledge of trauma surgery, providing hands-on operating experience, and organizing apprenticeship opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies assessing potential means of stimulating interest in orthopaedics and other surgical specialities among medical students have demonstrated that practical and interactive experiences during medical school effectively stimulate interest in pursuing a future surgical career. 2 , 9 , 15 These studies have highlighted the importance of positive interaction with surgical professionals: this can be teaching-based aimed at increasing clinical or career-based knowledge, take the form of interactive practical skills sessions, or via mentorship relationships between surgeons and students. A recent study in Brazil demonstrated the beneficial impact of societies tasked with increasing knowledge of trauma surgery, providing hands-on operating experience, and organizing apprenticeship opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Brazil demonstrated the beneficial impact of societies tasked with increasing knowledge of trauma surgery, providing hands-on operating experience, and organizing apprenticeship opportunities. 15 Similarly, in cardiothoracic surgery, interactive workshops involving guided dissection, surgical skills practice, and talks from surgeons, were shown to successfully increase interest in a career in surgery. 2 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…This showed that over 90 per cent of participants believed that participating in the society provided knowledge and information that the medical school curriculum could not provide and had positively influenced their career choice. 30 Although several undergraduate otolaryngology societies exist in the UK, not every medical school has one. Widespread availability of such societies and greater representation of otolaryngology within generic surgical societies should be facilitated by senior otolaryngologists in order to maximise undergraduate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunities for more surgeon-led practical experience need to be further integrated into the British medical school experience. Studies assessing how to stimulate interest in surgery amongst medical students have demonstrated that practical and interactive experiences of surgery during early medical school training effectively stimulate interest in pursuing a surgical career [4] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . What is key here is a positive interaction with surgical professionals: this can be teaching-based aimed at increasing clinical or career-based knowledge, take the form of interactive practical skills sessions, or via mentorship relationships between surgeons and students.…”
mentioning
confidence: 99%
“…A recent study in Brazil demonstrated the beneficial impact of ‘National Trauma Leagues’ on interest in surgery [7] . These ‘Leagues’ are surgeon-led University societies tasked with increasing knowledge of trauma surgery, providing hands-on operating experience, and organising apprenticeship opportunities.…”
mentioning
confidence: 99%